Pengaruh Periode Simpan Dan Konsentrasi Ekstrak Bawah Merah (Allium cepa L.) Terhadap Viabilitas Dan Vigor Benih Timun Apel (Cucumis SP.) - Nabilla Aprilia Harsono; Fawzy Muhammad Bayfurqon; Elia Azizah (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of the study was to obtain the treatment of the shelf period and the concentration of the best onion extract solution for viability and seed vigor of apple cucumber (Cucumis sp.). Research was conducted in October to January 2021 at the Agronomy Laboratory, Faculty of Agriculture, Karawang University of the Singaperbangsa. The research method used is the Complete Random Experimental method (RAL) 2 factors with 20 treatments. The first factors are the save period 0 weeks (S0), 4 weeks (S1), 8 weeks (S2), and 12 weeks (S3). The second factor is 0% onion extract concentration (B1), 25% (B2), 50% (B3), 75% (B4), 100% (B5). repeated 3 times so there were 60 experimental units. The observation results data is analyzed using variety analysis and in advanced tests with DMRT at a 5% degree. The results showed that there was no effect of interaction between the treatment of the shelf period and the soaking of the concentration of onion extract (Allium cepa L.) on the maximum growing potential parameter, germinating power, sluggish growing and seed growing speed. There are however real different interactions to the vigor index and the dry weight of the normal sprout. Self-sustaining treatment of the shelf period gives significant results to all parameters and immersion of the onion extract concentration (Allium cepa L.) does not give any real influence to all observation parameters. The best results are obtained in the save period of 0 weeks with immersion using 50% and 100% onion extract concentrations